Allá van leyes do quieren reyes (Guillén de Castro): poder absoluto y desengaño - Nathalie Peyrebonne (E-Spania, 2021)
Guillén de Castro’s play, Allá van leyes do quieren reyes, written circa 1600, features a despot who authoritatively cancels the wedding of one of his vassals so that he can marry his wife. It is an unremitting demonstration of the absolute power of the king, whose desires have the force of law, a common theme in plays at that time. However, unlike the other plays, including Guillén de Castro’s, this royal injustice does not lead to tyrannicide or even rebellion: it prevails and crushes its poor victims. What political lesson can be drawn, other than “might makes right”? We maybe should read the play from a different perspective. Guillén de Castro wrote it at a time when the conception of theater advocated by Virués was being replaced by la Comedia nueva. And it is in light of this literary context that the treatment of the political question in the play needs to be investigated, as the figure of the unjust king, coupled with the concept of desengaño, serves as a medium that could primarily be literary.